Career Development Strategy and Work Motivation in Improving Employee Performance through Organizational Commitment - Khaeruman Khaeruman; Siti Mariam (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to examine the influence of career development strategies and work motivation on employee performance, with organizational commitment serving as a mediating variable. A quantitative approach was employed, involving a population of 500 employees from a state-owned public transportation company. Data were collected from 100 selected respondents using a questionnaire that had been tested for validity and reliability. The analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results showed that career development strategies had a significant positive effect on employee performance, with a coefficient of 0.45, and on organizational commitment, with a coefficient of 0.50. Work motivation also positively influenced performance (coefficient 0.38) and organizational commitment (coefficient 0.42). Furthermore, organizational commitment was found to significantly mediate the influence of career development strategies on performance (coefficient 0.30) and the effect of work motivation on performance (coefficient 0.25). These findings indicate that enhancing career development strategies and work motivation can lead to improved employee performance, particularly through the strengthening of organizational commitment. This study also reinforces previous research highlighting the importance of career development programs and employee motivation in improving performance and fostering employee loyalty to the organization.